Evaluation of the Therapeutic Effect of a Flavonoid Prescription against Rabbit Hemorrhagic Disease In Vivo. (4th April 2019) - Du, Hongxu; Zhang, Shuaibing; He, Miao; Ming, Ke; Wang, Jinli; Yuan, Wenjuan; Qiao, Mingyu; Wu, Yi; Wang, Deyun; Hu, Yuanliang; Liu, Jiaguo
Abstract : Rabbit hemorrhagic disease (RHD) is an acute, high fatal contagious disease induced by rabbit hemorrhagic disease virus (RHDV) with acute severe hepatic injury and causes huge economic loss worldwide. In order to develop an effective and reliable drug to treat this disease in clinic, a prescription formulated with baicalin, linarin, icariin, and notoginsenoside R1 (BLIN) according to the theory of syndrome differentiation and treatment in traditional Chinese veterinary medicine was applied to investigate its curative effects against RHD in vivo . The preliminary study results showed that BLIN prescription exerted good curative effect on RHD therapy. To further validate the curative effect and to investigate the possible related curative mechanisms of this drug, the survival rates, the plasma biochemical indexes of hepatic function, the plasma evaluation indexes of oxidative injury, and the RHDV gene expression levels were detected and then the correlation among these indexes was also analyzed. These results showed that BLIN prescription could significantly increase the survival rate, reduce the hepatic injury severity, alleviate the oxidative injury, and decrease the RHDV gene expression level in rabbits infected with RHDV. All these results indicate that BLIN prescription possesses outstanding curative effect against RHD, and the curative mechanism may be related to its antioxidant and anti-RHDV activities. Therefore, this prescription can be expected to be exploited into a new candidate for RHD therapy in clinic.